Caribbean tourism, trends, policies and impact 1985-2002 (ECLAC Port of SpainTT, 2003)
Provides an overview of the structure and performance of the Caribbean tourism sector. Evaluates the role of policies and strategies as they impact the growth and competitiveness of the sector.
Keywords: TOURISM